The use of a percutaneous cystostomy tube as an adjunctive treatment option for dogs with idiopathic functional outflow tract obstruction - Zoe P. Greenfield; Allyson C. Berent; Chick W. Weisse (Journal of Veterinary Internal Medicine)
Abstract Background Functional outflow tract obstruction (FOO) remains a challenging disease to manage in male dogs. Cystostomy tubes have been used to relieve urethral obstruction while allowing time to achieve effective medical management, avoiding the need for emergency visits and repeat urinary catheterizations. Objectives To describe a series of dogs with FOO and categorize the most successful management strategies including medical management alone or with the support of cystostomy tubes for urinary diversion. Animals Twelve client‐owned dogs with FOO were included. Methods Medical records of dogs presented from August 2012 to September 2021 with a presumptive diagnosis of FOO were retrospectively reviewed and findings recorded. Results Seven dogs were managed with a cystostomy tube and 5/7 (71%) had a good‐excellent outcome. Five dogs were managed without a tube and 1/5 (20%) had a good outcome. Eight dogs were refractory to medical management; 5 managed with a cystostomy tube and 3/5 (60%) had a good‐excellent outcome; 3 managed without a cystostomy tube and 0/3 had a good or excellent outcome. Overall, dogs with cystostomy tubes had better outcomes but also had mild, moderate, and severe complications (100%, 71%, and 71%, respectively) reported. Conclusions and Clinical Importance Most dogs that received a percutaneous cystostomy tube as part of their management plan had a good to excellent outcome, particularly when compared to those that did not, despite the high rate of tube‐related complications. Percutaneous cystostomy tubes could be considered early during management for FOO to improve overall outcomes.